Preventing malicious accounts based on mining with steganography in online - K. Karpaga Priyaa, Ms; Lahari, Keerthipati; Vasundhara, V; Saranya, C (International Journal of Engineering and Technology, 2018)
On-line Social Networks (OSNs) are progressively exerting consequences on the way communication takes place among people through sites such as Twitter, Facebook, Google+ and LinkedIn, possessing millions of users. The Online Social Networks’ (OSN) users face security-privacy threats such as Profile cloning, privacy breach and malware attacks. By these attacks, the fake user steals the virtual identity of the original user which they use to interact with other online users. To prevent these attacks, the proposed system uses Steganography which is the process of hiding information within other non-secret text or data. Our proposed system utilizes Steganography by implementing Watermarking technique which hides a secret text inside an image invisibly. Moreover the system avoids the leakage of personal information and prevents the creation of fake accounts. Experimental results show that the proposed technique can effectively detect and prevent creating malicious accounts in comparison with the techniques reported previously.
Keywords: Fake accounts; Secret text; Steganography; Watermarking.